Business continuity communications : successful incident communication planning with ISO 22301 - Preen, Jim (BSI, 2012)
This book delivers extensive media and communications expertise in a practical and easy-to-follow format that will enable readers to put together a thorough incident communication plan that really works.
Keywords: Business communication.; Business communication -- Great Britain.; elektronické knihy; electronic books